2011
DOI: 10.1124/dmd.111.040725
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of KAI-9803, a Novel δ-Protein Kinase C Inhibitor, after Intravenous Administration to Rats

Abstract: ABSTRACT:KAI-9803 is composed of a selective ␦-protein kinase C (␦PKC) inhibitor peptide derived from the ␦V1-1 portion of ␦PKC (termed "cargo peptide"), conjugated reversibly to the cell-penetrating peptide 11-amino acid, arginine-rich sequence of the HIV type 1 transactivator protein (TAT 47-57 ; termed "carrier peptide") via a disulfide bond. KAI-9803 administration at the end of ischemia has been found to reduce cardiac damage caused by ischemia-reperfusion in a rat model of acute myocardial infarction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…It is a conjugate between the Drp1-dervied sequence in region 110 (cargo) and the cell-permeable peptide carrier TAT 47-57 , which has been widely used for cargo delivery in cultures and in vivo. Our previous studies showed that TAT-conjugated peptides can quickly enter cells and pass through the blood-brain barrier (Bright et al, 2004;Qi et al, 2008) and have extensive bio-distribution within minutes after single dose treatment in vivo and in cultures (Begley et al, 2004;Miyaji et al, 2011). Thus, P110 may be useful in treatment of diseases associated with excessive mitochondrial fission, such as Parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…It is a conjugate between the Drp1-dervied sequence in region 110 (cargo) and the cell-permeable peptide carrier TAT 47-57 , which has been widely used for cargo delivery in cultures and in vivo. Our previous studies showed that TAT-conjugated peptides can quickly enter cells and pass through the blood-brain barrier (Bright et al, 2004;Qi et al, 2008) and have extensive bio-distribution within minutes after single dose treatment in vivo and in cultures (Begley et al, 2004;Miyaji et al, 2011). Thus, P110 may be useful in treatment of diseases associated with excessive mitochondrial fission, such as Parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of preclinical and clinical trials that have been conducted (or are currently underway), no CPP or CPP conjugate has gained US Food and Drug Administration (FDA) approval as a cancer therapeutic. The CPP conjugate cyclosporinoctaarginine (PsorBan, by CellGate Inc.) has been used for topical therapy in psoriasis [80], and CPPs have also been used to treat wrinkles [81], minimize fibrosis or scarring [82], in myocardial infarction and spinal cord injury [83,84], inflammation [83,84], and many other therapeutic applications. A few clinical trials are currently underway that use CPPs for cancer therapy.…”
Section: Clinical Trials and Cppsmentioning
confidence: 99%
“…The conjugate entered Phase II clinical trial, which was eventually terminated in 2003. The modern CPP-vaccines were tested for myocardial infarction [92], spinal cord injury [93] and HIV vaccination. Other studies have been re performed in metastatic solid tumors [89] or in acute sensorineural hearing loss caused by cochlear injury [94].…”
Section: In Vivo Studies Of Cppsmentioning
confidence: 99%